Pengaruh Leverage, Likuiditas, Ukuran Perusahaan, Intensitas Aset Tetap Terhadap Revaluasi Aset Tetap Pada Perusahaan Infrastruktur - Marella Ajeng Maharani; Elsa Imelda (CV. Ulil Albab Corp, 2024)
The purpose of this study is to determine the effect of leverage, liquidity, company size, and fixed asset intensity on the revaluation of fixed assets of infrastructure companies listed on the IDX for the period 2018-2022. A total of 46 infrastructure companies that met the requirements provided 230 data points for the logistic regression analysis test. The research findings show that although company size and fixed asset intensity positively affect fixed asset revaluation, debt and liquidity factors have no effect. The implications of the research findings provide management with further information to take into account company size and fixed asset intensity when conducting fixed asset revaluations. This helps ensure that fixed assets are fairly valued and helps create easy-to-use financial reports.